Reflections on Professional Ethics in Social Work: Meeting point between of supervision of social work and social work in organizations - Buenaventura Rubio, María Antonia; Matulič Domandzic, María Virginia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article, the results obtained from the transversal activities on ethics carried out in the subjects of Supervision of Social Work I and Social Work in Organizations taught in the Social Work degree at the University of Barcelona are presented. The theoretical-practical reflection on the importance of ethics in the profession through the resolution of a case in both subjects and in the VI Conference on Social Work and Ethics and II on Transversality allows reflection on professional principles and values and ethics in the intervention within the organization.